Current status of pediatric intestinal transplant in Europe. Issue 2 (April 2020) - Andres, Ane M.; Ramos, Esther; Hernandez, Francisco
Abstract : Purpose of review: This review features articles published during 2018 and 2019 regarding pediatric visceral transplantation in Europe. In this biannual review, the authors identify and summarize key articles pertinent to clinical and research areas. Recent findings: There is a trend to a lower use of intestinal transplantation in pediatric population in Europe. Most articles were focused in long-term follow-up. The burden of the disease 10 years after intestinal transplantation is still significant, including the need of several medications, readmissions, and the need of specific follow-up, mostly because of psychiatric problems. Regarding eating behaviors, promoting eating pretransplant may be protective and there may be eating difficulty predictors that could be used to facilitate targeted interventions. Two different articles were consistent in the identification of C1q-fixing DSA as a marker of poor outcome, and capillaritis was identified as a predictor of C4d positivity in intestinal graft biopsies. The inclusion of the liver emerged as the main protective factor against dnDSA development. The incidence of PTLD (specially the monomorphic type) was significantly higher following ITx than after LTx (14.9 vs. 2.8%). The European societies and the EU have made an effort to promote networking, collaborative registries, and sharing of knowledge in pediatric transplantation. Summary: Recent articles focused mostly on long-term follow-up issues, although translational research has also been sustained by some groups.